2005
DOI: 10.1093/gerona/60.3.380
|View full text |Cite
|
Sign up to set email alerts
|

Reading Aloud and Arithmetic Calculation Improve Frontal Function of People With Dementia

Abstract: Our results indicate that learning tasks of reading aloud and arithmetic calculation can be used for cognitive rehabilitation of dementia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 34 publications
8
119
1
3
Order By: Relevance
“…Some studies (e.g., Niti et al, 2008;Verghese et al, 2003;2006) have demonstrated that there is an association between cognitive activity and memory performance. Intellectually stimulating activities, such as reading, playing mental games, and doing crossword puzzles, have been found to be associated with reduced dementia risk (Kawashima et al, 2005;Wilson et al, 2002). However, the results of the present longitudinal study do not confirm this.…”
Section: Discussioncontrasting
confidence: 98%
“…Some studies (e.g., Niti et al, 2008;Verghese et al, 2003;2006) have demonstrated that there is an association between cognitive activity and memory performance. Intellectually stimulating activities, such as reading, playing mental games, and doing crossword puzzles, have been found to be associated with reduced dementia risk (Kawashima et al, 2005;Wilson et al, 2002). However, the results of the present longitudinal study do not confirm this.…”
Section: Discussioncontrasting
confidence: 98%
“…Other activities such as cognitive training also improve cognitive function; those who took "brain training" using a personal computer significantly improved their memory function [24,25]. Reading aloud and doing math also improve frontal functions in dementia [26]. Looking at these previous studies, we see there are two major interventions that can improve cognitive function, namely exercise and cognitive training.…”
Section: Discussionmentioning
confidence: 91%
“…The control group showed no change in FAB score and a decline in MMSE score. 21 A larger study with an open design tested the Memory65+ computer training program, with 127 people with and without cognitive impairment. 22 Participants were tested at baseline, posttraining, and at 9 months.…”
Section: Brain Training Gamesmentioning
confidence: 99%